PENGARUH BELANJA MODAL TERHADAP BELANJA PEMELIHARAAN (STUDI EMPIRIS PADA PEMERINTAH DAERAH JAWA TIMUR) - Rustiyaningsih, Sri (Widya Warta, 2012)
This study aims to examine the effect of capital expenditure on maintenance expenditure in the same year, and in different years, by looking at changes of capital expenditure and maintenance expenditure. This research is a case study that examined the causal relationship between variables. The data used were panel data. They were the secondary data taken from budget realization reports of municipality and regency governments in the Province of East Java in 2004, 2005, and 2006. Hypothesis testing made use of a simple regression analysis. The analysis showed that significant capital expenditure significantly influenced maintenance expenditure in the same test. Capital expenditure, however, had no significant effect on maintenance expenditure with the data testing in different years. The increase in capital expenditure significantly influenced the increase in maintenance expenditure.